How well does wind speed predict air‐sea gas transfer in the sea ice zone? A synthesis of radon deficit profiles in the upper water column of the Arctic Ocean. Issue 5 (5th May 2017) - Loose, B.; Kelly, R. P.; Bigdeli, A.; Williams, W.; Krishfield, R.; Rutgers van der Loeff, M.; Moran, S. B.
Abstract: We present 34 profiles of radon‐deficit from the ice‐ocean boundary layer of the Beaufort Sea. Including these 34, there are presently 58 published radon‐deficit estimates of air‐sea gas transfer velocity ( k ) in the Arctic Ocean; 52 of these estimates were derived from water covered by 10% sea ice or more. The average value of k collected since 2011 is 4.0 ± 1.2 m d −1 . This exceeds the quadratic wind speed prediction of weighted kws = 2.85 m d −1 with mean‐weighted wind speed of 6.4 m s −1 . We show how ice cover changes the mixed‐layer radon budget, and yields an "effective gas transfer velocity." We use these 58 estimates to statistically evaluate the suitability of a wind speed parameterization for k, when the ocean surface is ice covered. Whereas the six profiles taken from the open ocean indicate a statistically good fit to wind speed parameterizations, the same parameterizations could not reproduce k from the sea ice zone. We conclude that techniques for estimating k in the open ocean cannot be similarly applied to determine k in the presence of sea ice. The magnitude of k through gaps in the ice may reach high values as ice cover increases, possibly as a result of focused turbulence dissipation at openings in the free surface. These 58 profiles are presently the most complete set of estimates of k across seasons and variable ice cover; as dissolved tracer budgets they reflect air‐sea gas exchange with no impact from air‐ice gas exchange. Plain Language Summary: This study shows how the rate of gas exchange between the ocean and atmosphere can be affected by the presence of sea ice. The rate of gas exchange is difficult to measure, but here we present 58 published estimates and synthesize what they can tell us. This rate is relevant to ocean and atmosphere budgets of methane, carbon dioxide, and other greenhouse gases. Key Points: We present previously overlooked details related to gas tracer budgets in the presence of sea ice Radon‐deficit estimates of k show statistically adequate fit to wind speed parameterizations, when measured in 100% open water Radon‐deficit estimates of k do not fit with wind speed parameterizations, when measured beneath sea ice cover